An Experimental Study of Bond Market Pricing - Matthias Weber; John Duffy; Arthur Schram (Tinbergen Institute, 2016)
An important feature of bond markets is the relationship between initial public offering prices and the probability of the issuer defaulting. First, this probability affects the bond prices. Second, IPO prices determine the default probability. Though market equilibrium has been shown to predict well for other assets, it is a priori unclear whether markets will yield competitive prices when such interaction with the default probability occurs. We develop a flexible bond market model that is easily implemented in the laboratory and examine how subjects price bonds. We find that subjects learn to price bonds well after only a few repetitions.
Keywords: C92; C90; D47; G12; 330; bond markets; experimental finance; experimental markets; asset pricing; learning